Análisis del impacto de la planeación estratégica y la estructura organizacional en la competitividad de la Empresa Serveis V&G S.A.S. (2022)
This project is developed in the company Serveis V&G SAS, dedicated to carrying out all the activities inherent to the publishing business, located in the Municipality of Facatativa, its study begins with the elaboration of a diagnosis using analysis tools such as PESTAL analyzing the factors that most impact the proper development of the work carried out in the company, as well as the DOFA matrix is ​​implemented for the identification of strategies that the company must carry out to increase its strengths, minimize its weaknesses, control threats and visualize opportunities.